Особливості будови елементарного пагона та пагонової системи чотирьох видів роду Coelogyne Lindl. (Orchidaceae Juss.) - Gyrenko, O.G.; Kovalska, L.A.; Tkachenko, G.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to investigate morphological peculiarities of elementary shoot of four species of the genus Coelogyne Lindl. (iJuss.): C. fimbriata Lindl., C. flaccida Lindl., C. huettneriana Rchb.f., C. viscosa Rchb. f. Material and methods. The raw material derived from living plant collections of the M.M. Gryshko National Botanical Garden, of the NAS of Ukraine. The study of vegetative and reproductive organs was performed by dissection and study of buds and shoots using “STEMI 2000-C”. To characterize vegetative and generative organs used atlas on descriptive morphology of higher plants. Results. Rhizome part of shoot consists from 7 (C. huettneriana) to 15 (C. fimbriata) meromes, on which are formed from 2 (C. viscosa) to 4 (C. flaccida) axillary buds; orthotropic vegetative part consists of 3–4 meromes. Generative part of C. fimbriata develops only after complete formation of the pseudobulb and leaves and from the upper bud develops a shoot of the next branching order. From the upper bud of C. huettneriana develops a shoot with synanthous type of inflorescence. From the upper bud of C. viscosa forms the inflorescence before develops a vegetative part of shoot. From the upper bud of C. flaccida develops a shoot, which completely forms only a generative part, and from below bud develops a shoot of renovation. Conclusions. The obtained results indicate that of C. fimbriata plants have the vegetatively-generative elementary shoot with hysteranthous inflorescence and mono- and dichasial branching type, C. huettneriana plants — synanthous developmental inflorescence type and monochasial branching type, supposing the long shoot chain formation, C. viscosа plants — proteranthous type of inflorescence development and mono- and dichasial type of shoot, C. flaccida plants — heteranthous type of inflorescence development the dichasial branching shoot was observed. It was found that each shoot of C. flaccida initiated the development of two shoots. The simultaneous development of three shoots in C. flaccida is considered rather as an exception.